ANALYSIS OF BILDUNGSROMAN ELEMENTS IN “THE CRUEL PRINCE” BY HOLLY BLACK: ALIGNMENT AND DEVIATION - Chal Goma; Stephani Johana Sigarlaki; Muh. Hasan Basri (Universitas Sam Ratulangi, 2025)
This research focused on the alignment and deviation of Bildungsroman element in “The Cruel Prince”. This research aims to identify the Bildungsroman elements that presents in “The Cruel Prince” as well as analyze the alignment and deviation of those elements with classical Bildungsroman tradition. This research utilized the qualitative descriptive method, Golban (2003) theory of Bildungsroman, and Stanton (1965) theory of narrative element. The results found that “The Cruel Prince” contains all ten elements of the Bildungsroman as outlined in Petru Golban’s (2003) framework, while simultaneously transforming these elements to reflect contemporary concerns and fantasy genre conventions. Through systematic analysis of plot, character, and setting elements, this research reveals a complex pattern of preservation and innovation that characterizes contemporary fantasy coming-of-age narratives. This study is limited to the first book of “The Folk of the Air” trilogy by Holy Black.